Experimental study in the dry high-speed turning of AISI 316L stainless steel - Morales Tamayo, Yoandrys; Zambrano Robledo, Patricia; Pérez Rodríguez, Roberto; ívila-RondónRicardo; Hernández González, Luis; Zamora Hernández, Yusimit (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
The current experimental study is focused on investigating the effects of cutting parameters on flank wear in two coated carbide inserts during dry high speed finish turning of AISI 316L stainless steel. The effects of cutting parameters were determined using analysis of variance and simple regression. As a main result a significant effect of cutting feed and the machining time on flank wear was found. The three coating layers insert did not exceed the criterion of end of life of wear while the insert with one layer suffered a catastrophic wear at the highest cutting speed. The flank wear showed the best performance for the cutting feed of 0.08 mm/rev at all the speeds used in the study.